(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to determine the average intraperitoneal pressure (IPP) in peritoneal dialysis patients in the supine, sitting, and standing positions and to identify factors related to IPP. Methods: We conducted a retrospective, descriptive study on 87 chronic kidney disease patients undergoing chronic peritoneal dialysis at An Giang Central General Hospital from February to September 2024. Intraperitoneal pressure was measured using Durand’s method in the supine, sitting, and upright positions. Results: The study included 87 patients (45 female, 42 male) with an average age of 49.5 ± 1.5 years and a BMI of 22.13 ± 0.34 kg/m². The mean supine IPP was 14.7 ± 0.25 cmH₂O. IPP in the sitting and upright positions was similar and approximately 12 cmH₂O higher than in the supine position. Supine IPP ≥ 14 cmH₂O was found to be significantly related to BMI (p < 0.015) and intraperitoneal volume (p < 0.0005). Multivariate linear regression analysis showed no significant relationship between IPP and BSA, peritoneal dialysis time, waist-to-hip ratio, Charlson comorbidity index, or gender (p > 0.05). There were 10 cases of mechanical complications (9 abdominal wall hernias, 2 inguinal hernias), but no statistically significant association with increased IPP. Conclusion: Our findings suggest that IPP is an individual value related to body size and intraperitoneal volume. Measuring IPP is a simple, safe technique that can aid in prescribing peritoneal dialysis, especially for obese patients.